Perfluoroalkyl substances in the environment and biota from the coasts of the South China Sea: profiles, sources, and potential risks - Zhang, Jiaer; Xie, Yuxin; Zhang, Jingru; Ye, Mai; Diao, Jieyi; Wang, Jianwen; Sun, Qiongping; Wang, Tieyu (Frontiers in Environmental Science, 2024)
Perfluoroalkyl substances (PFAS) are emerging contaminants that have been produced since the 1950s. The first paper on PFAS was published in 2001, raising global concern. Since then, many countries have implemented policies to control PFAS. In this study, we surveyed PFAS in water, sediment and biota in coastal areas to review the use of PFAS since their first production using chronological methods, combined with the implementation of previous policy restrictions on PFAS. In the meantime, report on existing PFAS to assess the ecological and health risks of seafood consumption by coastal populations. Following the restrictions on PFAS, the concentration of PFAS has been steadily decreasing. With regard to the current occurrence of PFAS in water and sediment, there was almost no ecological risk. However, there are still risks of exposure to PFOS in different gender and age groups, which require constant monitoring. It is expected that the negative impact of PFAS on the environment and human health will continue to decrease with the implementation of the Chinese government's emerging pollutants control policy in 2023.Introduction